Factores sociodemográficos asociados a interrupciones de embarazo en el municipio Mayarí. Enero- junio del 2021 - Kirenia Aldana Zapata; Silvia María Pérez Pérez; Barbara Rodríguez Valenzuela; Niumila Merencio Leyva (Correo Científico Médico, 2023)
RESUMEN